The Existence of Human Rights in A Shift in The Concept of The State of Law - Siswadi, Imran; Supriadi, Supriadi (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
Human rights have become an essential element in international politics, especially after the end of the Cold War in the 1990s. The problem in this research is